SENTIMENT ANALYSIS OF CUSTOMER REVIEWS ON E-COMMERCE APPLICATIONS: LAZADA, TOKOPEDIA, AND BLIBLI - Ihza, Andika; Arifin, Muhammad; Setiawan, Arif (Lembaga Penelitian dan Pengabdian Kepada Masyarakat (LPPM) STMIK Royal Kisaran, 2026)
Abstract: The rapid growth of e-commerce in Indonesia has increased consumer interactions with digital platforms, particularly Lazada, Tokopedia, and Blibli, resulting in a large volume of customer reviews that reflect consumer experiences and perceptions but have not been optimally utilized in business decision-making. The main issue addressed in this study is how to process customer review data to generate meaningful information regarding consumer opinions. This research aims to apply web scraping techniques to collect customer review data and conduct sentiment analysis to identify trends in consumer opinions across the three e-commerce platforms. The dataset consists of 3,000 customer reviews, with 1,000 reviews collected from each platform, covering aspects such as shopping experience, service quality, delivery process, and customer satisfaction. The research methodology includes data collection through web scraping, text preprocessing for data cleaning and normalization, sentiment analysis using machine learning approaches, and visualization of sentiment results. The findings indicate differences in the distribution of positive, negative, and neutral sentiments across platforms, reflecting variations in consumer experiences and service strategies. These results demonstrate that sentiment analysis based on customer reviews can serve as strategic input to improve service quality, business performance, and marketing strategies in Indonesia’s e-commerce sector. Keywords: customer reviews; digital services; e-commerce; sentiment analysis; web scarping Abstrak: Pertumbuhan pesat e-commerce di Indonesia meningkatkan interaksi konsumen dengan platform digital, khususnya Lazada, Tokopedia, dan Blibli, yang menghasilkan ulasan pelanggan dalam jumlah besar sebagai cerminan pengalaman dan persepsi konsumen, namun belum dimanfaatkan secara optimal dalam pengambilan keputusan bisnis. Permasalahan utama penelitian ini adalah bagaimana mengolah data ulasan tersebut agar dapat memberikan informasi yang bermakna mengenai opini konsumen. Penelitian ini bertujuan menerapkan web scraping untuk mengumpulkan data ulasan pelanggan serta melakukan analisis sentimen guna mengidentifikasi tren opini konsumen pada ketiga platform e-commerce tersebut. Data yang digunakan berjumlah 3.000 ulasan pelanggan, dengan masing-masing platform diwakili oleh 1.000 ulasan yang mencakup pengalaman berbelanja, kualitas layanan, proses pengiriman, dan tingkat kepuasan pelanggan. Metode penelitian meliputi pengambilan data menggunakan web scraping, pra-pemrosesan teks untuk pembersihan dan normalisasi data, analisis sentimen dengan pendekatan pembelajaran mesin, serta visualisasi hasil sentimen. Hasil penelitian menunjukkan adanya perbedaan distribusi sentimen positif, negatif, dan netral pada setiap platform, yang mencerminkan variasi pengalaman konsumen dan strategi layanan. Temuan ini menunjukkan bahwa analisis sentimen berbasis ulasan pelanggan dapat menjadi masukan strategis untuk meningkatkan kualitas layanan, kinerja bisnis, dan strategi pemasaran e-commerce di Indonesia. Kata kunci: customer reviews; digital services;e-commerce;sentiment analysis;web scarping